To Save Our Species But How Do We Make Collective Decisions? - Emerson, Peter (European Scientific Journal, ESJ, 2017)
Throughout human history, havoc has been wrought by just a handful of very powerful leaders. The ultimate catastrophe could also be caused by just a few individuals, by unleashing a nuclear war or by ignoring international agreements on climate change. Donald Trump, for example, may renege on the Paris Agreement and commit other ecological blunders, which could spell the end for everyone. In a nutshell, the current democratic process gives him far too much power. The rights of any one citizen or country must be tempered by the rights of all. Alas, current forms of decision-making often fail to involve everyone in the final decision, the most obvious instances relating to decisions taken by a (simple or weighted) majority vote. If instead decision-making were based on the local, national or international consensus, such exclusive decisions could not be taken so easily. It should also be pointed out that majoritarianism – majority rule based on majority voting – has been and still is problematic in numerous inter-communal conflicts. This paper therefore outlines the flaws involved in binary voting; next, as a better methodology, it proposes a more inclusive voting mechanism; and finally, it advocates a structure to ensure that agreements are implemented, with possible penalties for those individuals, organisations or countries that flaunt the international consensus.